Inovasi Penambahan Daun Sirsak Terhadap Mutu Dan Daya Terima Konsumen Pada Produk Cheesecake - Ahmad Shulton Rahmatul Iman; Ita Fatkhur Romadhoni; Qorry’ Aina; Mafisa Restami (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to develop functional food innovations of cheesecake products based on local ingredients using soursop leaf extract (Annona muricata L.), analyze the effect of different concentrations on hedonic quality, and determine the chemical content of selected final products. The method used was a pure experiment with a single factor Completely Randomized Design (CRD) consisting of three treatments of soursop leaf extract concentrations, namely T1 (3 ml / 0.5%), T2 (6 ml / 1.0%), and T3 (9 ml / 1.5%) of a total dough of 634 grams, followed by a hedonic test using a 5-point preference scale involving 35 panelists. The results of statistical analysis using the One-Way ANOVA test and Duncan's further test showed that differences in extract concentrations had a significant effect on color, aroma, texture, and taste parameters (p < 0.05), but did not significantly affect overall preference. The best formulation was obtained in treatment T2 (6 ml) with the highest overall preference score (4.26) and the characteristics of an even bright green color (4.03), aroma (3.77), soft-compact texture (4.09), and savory-fresh taste (4.06). The results of the proximate analysis of the best formula (T2) showed nutritional content in the form of energy of 308.88 kcal/100g, ash content of 1.50%, carbohydrate 31.21%, protein 5.33%, fat 18.08%, and water content of 43.88%. This study concluded that the innovation of cheesecake products with the addition of soursop leaf extract of 6 ml has great potential to be accepted by the wider public and has a proportional macronutrient value profile.